Commentary on the constitution of India - Basu, Durga Das (Calcutta, 1993)
The present volume A contains an elaborate introduction to the entire series, including an illuminating discourse on the rules of interpretation. It contains, besides, an epitome of the entire series with case-law upto 1993, which no reader can dispense with.
Keywords: Constitutions